Inovasi Olahan Pepaya Lokal untuk Mendukung Ekonomi Rumah Tangga di Desa Ciampanan - Purnama, Wikal; Sulaeman Hariri, Zidan; Firda Silvia, Vivi; Haliza Dewi, Nur; Ramaniya Maharani, Syahla; Nur Aulya, Fasya; Hawanun Azzahra, Adilla; Amalina Putri Nugraha, Razita; Femilia, Dela; Amalia, Reva; Dwi Hanafian, Maulana; Alya Nurfauziah, Zahwa; Prastika, Nida; Mulyadi, Adi; Azzahra, Nazwa; Putra Pratama, Akmal; Pangestu, Andhika; Syahran Mawarid Taslim, Muhammad; Apriyani, Mutia; Noer Aprilyani, Suci; Mulyani, Eva (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2026)
Ciampanan Village has abundant local papaya resources; however, their utilization remains limited as papaya is mostly sold as fresh fruit while the seeds are discarded as waste. This community service program aimed to enhance the added value of papaya through innovation in processing papaya seeds into herbal tea and papaya fruit into jam. The implementation method involved participatory approaches through observation, hands-on training, and community mentoring. The results showed an increase in community knowledge and skills in processing local food products. Participants were able to produce papaya jam and papaya seed tea that are feasible for consumption and have potential to be developed as household-scale businesses. This program demonstrates that optimizing local agricultural resources can support economic empowerment and sustainable rural development.